2017
DOI: 10.1177/0033294117746990
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Suicide Ideation in Iranian Cardiovascular Patients: Testing the Mediating Role of Patience

Abstract: The aim of the present study was to explore the mediating role of patience on the relationship between mindfulness and suicide ideation. To do so, 110 patients with cardiovascular diseases were recruited from the outpatient Clinic of Imam Reza in the city of Shiraz in Iran. These patients completed The Five Facets Mindfulness Questionnaire, Patience Scale, and Suicide Ideation Questionnaire. Data were analyzed using structural equation modeling. Results indicated a significant positive relationship between min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Compared to gratitude, fewer studies have examined the relation between patience and suicide risk, with only one study examining the relation directly. Hashemi et al (2018) found patience negatively correlated with concurrent suicidal ideation among Iranian cardiovascular patients, who tend to have heightened suicide risk. Beyond this, research among psychiatric inpatients is illuminating.…”
Section: Suicidality and Struggles With Meaningmentioning
confidence: 83%
See 2 more Smart Citations
“…Compared to gratitude, fewer studies have examined the relation between patience and suicide risk, with only one study examining the relation directly. Hashemi et al (2018) found patience negatively correlated with concurrent suicidal ideation among Iranian cardiovascular patients, who tend to have heightened suicide risk. Beyond this, research among psychiatric inpatients is illuminating.…”
Section: Suicidality and Struggles With Meaningmentioning
confidence: 83%
“…However, there is some evidence that these findings might persist in less or differently religious settings and across diverse cultures and ethnicities given the persistent association between gratitude and suicide risk in samples outside the United States (Jung & Han, 2017;Lau & Cheng, 2017;Li et al, 2012;Lin, 2015;Ng & Wong, 2012;Rey et al, 2019;Varaee et al, 2019). Though far less numerous, international studies on patience also suggest the moderation by life hardships patience replicate across cultures (Hashemi et al, 2018;Valikhani et al, 2017). Only one relevant study on patience has been conducted in a primarily secular context (Wang et al, 2019), and it did not assess suicide risk or mental health symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, research shows patience is an important predictor of both eudaimonic and hedonic well-being (Schnitker, 2012; Schnitker, Ro, et al, 2019; Thomas & Schnitker, 2017), and multiple previous studies have demonstrated connections between patience and religiousness (e.g., Schnitker & Emmons, 2007; Schnitker et al, 2017). Scientists from nonwestern cultures include elements of transcendence in the operationalization of patience (Hashemi, Moustafa, Rahmati Kankat, Valikhani, 2018; Khormaei, Farmani, & Soltani, 2015; Valikhani, Moustafa, & Karimi, 2017). 1…”
Section: The Virtue Of Patience and Sportmentioning
confidence: 99%
“…Patience is defined as the ability to remain calm during times of difficulty, frustration, or suffering (Schnitker, 2012). The importance of patience has also been proven by various previous studies, including creating well-being (Chakhssi et al, 2018), reduce depression (Heslin, Elixhauser, & Steiner, 2012), fortification against suicidal ideation (Hashemi et al 2018). Likewise, the coping strategy developed for children is to pay in instalments to complete school assignments, not accumulate and tell stories with the family about the problems.…”
Section: Researchmentioning
confidence: 99%